Implementation of the PROMIS-29 in Routine Care for People With Diabetes: Challenges and Opportunities. Issue 4 (October 2018) - Scholle, Sarah Hudson; Morton, Suzanne; Homco, Juell; Rodriguez, Kristin; Anderson, Daren; Hahn, Elizabeth; Kendrick, David; Bardach, David; Hart, Elizabeth
Abstract : Using patient-reported outcome measures (PROMs) in care planning has the potential to improve care, but information about routine implementation in settings serving disadvantaged groups is needed. Two primary care clinics serving populations predominantly eligible for Medicaid and diverse in race/ethnicity implemented the PROMIS-29 as part of clinical care planning. Of the target population with diabetes, 26% (n = 490) completed the PROMs; the proportion that set a goal based on the PROMs differed by site. This report describes factors influencing the PROMs process and the results of interviews with patients and members of the care team about PROMs' implementation and impact.